Protective Effect on Pancreatic Acinar Cell by Maintaining Cardiac Output in Canine Heart Failure Model With Decreased Pancreatic Blood Flow - Yoshimura, Aritada; Ohmori, Takahiro; Hirao, Daiki; Kishimoto, Miori; Iwanaga, Tomoko; Miura, Naoki; Suzuki, Kazuhiko; Fukushima, Ryuji (Frontiers in Veterinary Science, 2022)
Heart failure cause hypoperfusion-induced damage to abdominal organs due to decreased cardiac output (CO). Using a model dog with heart failure caused by rapid ventricular pacing (RVP), we have previously demonstrated that a decrease in CO reduces pancreatic blood flow (PBF). Furthermore, we have revealed that pancreatic acinar cell atrophy, which is a change in the pre-stage of pancreatitis was caused. However, the mechanism by which pancreatic acinar cell atrophy was caused in RVP dogs remains unknown. This study aimed to clarify the association between cardiac function, PBF, and histopathological changes in pancreatic acinar cells by administrating pimobendan, which increase CO, to RVP dogs. RVP dogs were divided into the control group (no medication, n = 5) and the pimobendan group (pimobendan at 0.25 mg/kg BID, n = 5). Noninvasive blood pressure measurement, echocardiography, and contrast-enhanced ultrasonography for PBF measurement were performed before initiating RVP and at 4 weeks after initiating RVP (4W). At 4 W, the decreases in CO, mean blood pressure and PBF due to RVP were suppressed in pimobendan group. Furthermore, histopathological examination showed no changes in pancreatic acinar cells in the pimobendan group. Overall, it was clarified that the decrease in PBF due to cardiac dysfunction was a direct cause of pancreatic acinar cell atrophy. This suggests that maintaining PBF is clinically important for treating dogs with heart failure. In addition, these findings offer a reliable basis for developing new therapeutic strategies for heart failure in dogs, that is, pancreatic protection.